2005
DOI: 10.1016/j.clpt.2004.12.240
|View full text |Cite
|
Sign up to set email alerts
|

A population pharmacokinetic (PK) analysis of ABX-IL8, a fully human monoclononal IGG antibody, in psoriasis patients

Abstract: Background/Aims ABX‐IL8 is a fully human IgG2 monoclonal antibody generated using transgenic XenoMouse® technology that binds to human interleukin‐8 with high affinity and specificity, and has been evaluated in various inflammatory diseases. The objective of this investigation was to develop a population PK model for ABX‐IL8 in psoriasis patients. Methods In this analysis, 878 PK observations from 81 psoriasis patients were pooled from 2 clinical trials and analyzed simultaneously using NONMEM. One study was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Similarly, ABX-IL8 is a fully human IgG 2 monoclonal antibody that binds to human IL-8 with high affinity and specificity and is currently in Phase II clinical investigation for treatment of psoriasis by Abgenix (Fremont, CA, USA). 38 Strikingly, Kim et al 39 found that pretreatment with fluvastatin and simvastatin inhibited migration of human CD4 + T cells towards CCL20 in a chemotaxis migration assay. These findings suggest that these drugs may be of benefit in alleviating psoriasis via interrupting the CCL20/chemokine receptor 6 (CCR6) chemotactic interaction, thus inhibiting infiltration of T H 17 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ABX-IL8 is a fully human IgG 2 monoclonal antibody that binds to human IL-8 with high affinity and specificity and is currently in Phase II clinical investigation for treatment of psoriasis by Abgenix (Fremont, CA, USA). 38 Strikingly, Kim et al 39 found that pretreatment with fluvastatin and simvastatin inhibited migration of human CD4 + T cells towards CCL20 in a chemotaxis migration assay. These findings suggest that these drugs may be of benefit in alleviating psoriasis via interrupting the CCL20/chemokine receptor 6 (CCR6) chemotactic interaction, thus inhibiting infiltration of T H 17 cells.…”
Section: Discussionmentioning
confidence: 99%